Rationing of fuel consumption based on identification of rolling stock modes (Nexo Revista Científica, 2021)
The article presents the results of a study of innovative technology on improving the rationing of diesel fuel consumption on rolling stock in the railway industry. As an object of research, fuel consumption was studied on a Automotrisa diesel editing - ADE-1, which is used in the electrification and power supply facilities of the Transenergo Directorate. Motorized carriage loading transport (MLT – 6), which is used in the economy of the track. On the basis of a number of regulatory documents of the Russian Railways company, the Samara State University of Railway Transport was entrusted with the analysis of the efficiency of fuel consumption of SSPS on these types of rolling stock at one of the railway landfills. The special self-propelled rolling stock of the Russian Railways company was studied as an object of research. The method of forming fuel consumption standards by identifying the actual values of fuel consumption and indicators of rolling stock operating modes is considered. The statistical methods used in the research allow us to set the rate of consumption in the range of 8% of the actual flow rate. Based on the use of the obtained fuel consumption rate, a method for identifying and evaluating the level of unauthorized fuel overspendings (draining) is provided.